Assessing Rubber Intercropping Strategies in Northern Thailand Using the Water, Nutrient, Light Capture in Agroforestry Systems Model - Pansak, Wanwisa (Agriculture and Natural Resources, 2015)
The Water, Nutrient, Light Capture in Agroforestry Systems (WaNuLCAS) model was used to evaluate and understand the impact of crop management on intercropping scenarios and competition between rubber and associated annual crops. The intention was to identify sustainable production systems with economic benefits for small-scale landholders in Thailand. The WaNuLCAS model was used to predict maize and rubber productivity under various management scenarios of intercropping and sole cropping in the Phitsanulok province (16o55' N, 100o32' E), Thailand. Model scenarios were simulated for rubber (clone RRIM600) grown with spacings of 2.5 × 7 m, 3 × 7 m and 3 × 8 m under sole cropping and intercropping with maize. The yield of maize was substantially influenced by rubber-tree spacing in the intercropping systems. After 3 yr, the average yield of maize was decreased from 7 to 3 t.ha-1 by rubber tree growth if organic fertilizer was not applied. Organic fertilizer application mitigated the negative influences of rubber trees until the seventh cropping season. After 8 yr, the maize yield decreased to 0.4 t.ha-1. Hence, rubber intercropped with maize with the application of recommended chemical fertilizer plus organic fertilizer was the best way to mitigate competition between rubber and maize. In the long term, the rubber tree girth and wood volume from sole cropping were higher than from the rubber intercropping systems. With a higher rubber tree density, the rubber tree girth and wood volume increased more slowly.